First experience in implementing PBL for network design and management course - Noor, R.M.; Hussin, N. (2004)
This paper described the first experience in implementing PBL for a course in Network Design and Management (WRES3308) at the Faculty of Computer Science and Information Technology (FCSIT), University of Malaya in November 2002. A total of 83 students were involved, which was divided into smaller groups of 4 to 5 students. Each group were given issues or problems that they had to understand, discuss and find solutions. The students were prompted to identify skills and knowledge that were related to the subje ct given. The evaluation methods used throughout the course were based on student’s presentation, student’s learning journal, participation in group discussion, final group problem report, and group’s discussion, communication, and contributions. The PBL approach was found to direct student’s learning experiences in a challenging way.